Allelopathic effect of Euphorbia guyoniana aqueous extract and their potential uses as natural herbicides - Nasrine, S.; El-Darier, S.M.; El-Taher, H.M. (Universiti Kebangsaan Malaysia, 2013)
The aim of the present study was to investigate the potential allelopathic effects of Euphorbia guyoniana (donor species) aqueous extract on germination efficiency of two weeds (Bromus tectorum and Melilotus indica) and one crop species (Triticum aestivum) under laboratory conditions. The germination efficiency, plumule and radicle length of Bromus was completely inhibited at the highest concentration of aqueous extracts of the donor species level (10%). The two recipient species exerted weak measures as affected by the highest concentration level of the donor. This inhibition was markedly obvious in B. tectorum than in M. indica indicating that B. tectorum is more sensitive to the tested donor, while the M. indica is more adapted to the aqueous extract than the B. tectorum.